Research on the Design Logic and Implementation Pathways of the Triangular Classroom Teaching Model in Chinese Universities under the Digital Intelligent Context - Weiguaju Nong; Yan Wang; Jian-Hong Ye (Environment and Social Psychology, 2026)
The digitalization of teaching model is a key pathway to enhance university students’ learning quality and efficiency. However, current problems exist in Chinese universities including insufficient application of digital technologies, a predominant one-way knowledge transmission model, and inadequate teacher-student interaction. Based on the PAD Class Model and integrated with Bandura’s Reciprocal Determinism, this study incorporates generative AI/AI agent into teaching process to construct a “Triangular Classroom Teaching Model”. This model establishes three stages during the teaching process: “self-preparation (human-machine interaction), teacher-student interaction, and peer discussion (student-student interaction)” to address the limitations of the PAD (Presentation-Assimilation-Discussion) Class Model, such as the lack of preparation and real-time feedback, through the interplay of environment (digital technology), individuals (students), and behavior (learning). During the self-preparation stage, generative AI/AI agent facilitate student-led inquiry. In the teacher-student interaction stage, they enable data-driven analytics and tailored instruction. Finally, during peer discussions stage, they serve as cognitive tools to expand students’ cognitive horizons. The “Triangular Classroom Teaching Model” implements the “student-centered” philosophy through multi-dimensional collaboration, improving teaching quality and learning efficiency, and providing an operable innovative paradigm for the digitalization of teaching model in Chinese universities.